2019
DOI: 10.1007/s12298-019-00681-5
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of cadmium-induced genotoxicity and cytotoxicity by calcium chloride in faba bean (Vicia faba L. var. minor) roots

Abstract: Alleviation of cadmium-induced root genotoxicity and cytotoxicity by calcium chloride (CaCl 2 ) in faba bean (Vicia faba L. var. minor) seedlings were studied. Faba bean seeds were treated with H 2 O or 2% CaCl 2 for 6 h before germination. Seeds were then exposed to 0 and 50 lM CdCl 2 concentrations for 7 days. Genotoxic damaging effects of Cd was examined through the determination of the mitotic index (MI), chromosomal aberrations (CA) and micronucleus (MN) in the meristem cells of faba bean roots. Similarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 69 publications
(60 reference statements)
2
8
0
1
Order By: Relevance
“…Ca is an important macronutrient for plants and plays a significant regulatory role in the growth and development of plants and in the response to abiotic stress . The positive effects of Ca on plant growth under Cd exposure have long been confirmed as a result of Cd–Ca antagonism. This study also showed similar results that 10 mM Ca ameliorated the toxicity of Cd, whereas the toxicity was enhanced when supplemented with 0.5 mM Ca (Figure ).…”
Section: Discussionsupporting
confidence: 67%
“…Ca is an important macronutrient for plants and plays a significant regulatory role in the growth and development of plants and in the response to abiotic stress . The positive effects of Ca on plant growth under Cd exposure have long been confirmed as a result of Cd–Ca antagonism. This study also showed similar results that 10 mM Ca ameliorated the toxicity of Cd, whereas the toxicity was enhanced when supplemented with 0.5 mM Ca (Figure ).…”
Section: Discussionsupporting
confidence: 67%
“…The second possible cause would be related to the disrupted PM structure causing increased H + passive permeability. The latter hypothesis was sustained by the Cd-induced decrease of phospholipid unsaturation degree (Nouairi et al 2019). Cadmium could directly modify the activity of membrane-bound enzymes through the formation of Cd 2+ -protein complexes and the replacement of Ca 2+ in membrane essential sites (Chen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metal (HM) contamination of agricultural lands is becoming a significant threat to the sustainability of agroecosystems (Ashraf et al 2017;Wang et al 2017;Wani et al 2018;Ali et al 2018;Vardhan et al 2019;Zaid et al 2019b). Cadmium (Cd), one of the HMs, is a non-essential element, very toxic to plants (Wang et al 2018;Nouairi et al 2019;Rizwan et al 2019;Zaid et al 2019b). Nearly 20 million hectares of cultivable land worldwide are known to be contaminated by Cd (Liu et al 2015;Dong et al 2017).…”
Section: Introductionmentioning
confidence: 99%